Relationship as seen through letter-writing style in Van Gogh’s letters to Gauguin - Farah Anindya MAHARANI; Myrna Laksman-Huntley (FRANCISOLA, 2022)
RÉSUMÉ.  Van Gogh a tenté de former une communauté avec Gauguin. Cet article parle de leur relation dans des lettres de VG. Le choix des mots, le style de langue, la structure des lettres et les fonctions syntaxiques utilisées dans les phrases de ses lettres ont été extraits des six lettres de VG et analysés à l'aide d'une méthode qualitative, l'approche de l’ACD et de la théorie des fonctions syntaxiques françaises de Le Querler. L’amitié respectueuse est construite par la politesse mais pas complètement formelle. Cette relation asymétrique se reflète à travers la diction contrastée, le choix des pronoms et des salutations, l'utilisation d'un langage implicite et aussi par l'expansion de la structure de la phrase pour être plus poli. Grâce au style d'écriture de lettres de VG, leur relation évolue d'une transaction à quelque chose de plus personnel. Les différences d'ancienneté et de réputation sont souvent devenues un facteur influençant les relations et la communication. Mots-clés : analyse critique du discours, Gauguin, style de langage, fonction syntaxique, van GoghABSTRACT.  Van Gogh, the Dutch post-impressionist painter, tried to form a community with Gaugin, the French post-impressionist painter, printmaker and sculptor. This article studied VG’s relationship with Gauguin in letters written by VG. The words choice, language style, letter structure, and syntactic functions used in the sentences of his letters were extracted from VG’s six surviving letters and analyzed using a qualitative method, CDA approach and Le Querler’s French syntactic functions theory. We discover that VG tried to build a respectful friendship through politeness but not completely in a formal language style. This asymmetrical relationship reflects through the contrasting diction, choice of pronouns and greetings, the use of implicit language and also by expansion in the sentence structure to be more polite. Through VG’s letter-writing style, their relationship evolves from being transactional into something more personal. Seniority and reputational differences often became a factor influencing relationships and communication.Keywords: critical discourse analysis, Gauguin, language style, syntactic function, van Gogh